2014
DOI: 10.1155/2014/272376
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis: An Overview and Therapeutic Options

Abstract: Sporotrichosis is a chronic granulomatous mycotic infection caused by Sporothrix schenckii, a common saprophyte of soil, decaying wood, hay, and sphagnum moss, that is endemic in tropical/subtropical areas. The recent phylogenetic studies have delineated the geographic distribution of multiple distinct Sporothrix species causing sporotrichosis. It characteristically involves the skin and subcutaneous tissue following traumatic inoculation of the pathogen. After a variable incubation period, progressively enlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
194
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(225 citation statements)
references
References 103 publications
4
194
0
13
Order By: Relevance
“…70% of our positive cases had a definite history of trauma with thorns, straw etc. 60% of our cases had lymphocutaneous variety which correlate well with study of Mahajan et al, (2014) who also found lymphocutaneous variety to be the commonst. microscopic detection of S. Schenckii in biopsy sections and Pus is always difficult (Sanyal et al, 1973;Kaufman, 1999) as also observed in our case.…”
Section: The Chances Of Isolating Sporothrix Schenckiisupporting
confidence: 91%
“…70% of our positive cases had a definite history of trauma with thorns, straw etc. 60% of our cases had lymphocutaneous variety which correlate well with study of Mahajan et al, (2014) who also found lymphocutaneous variety to be the commonst. microscopic detection of S. Schenckii in biopsy sections and Pus is always difficult (Sanyal et al, 1973;Kaufman, 1999) as also observed in our case.…”
Section: The Chances Of Isolating Sporothrix Schenckiisupporting
confidence: 91%
“…A cultura e identificação de espécies de Sporothrix é considerada por muitos autores como sendo a técnica padrão-ouro de diagnóstico (Schubach et al 2012, Mahajan 2014). Entretanto, a falta de suspeita clínica faz com que amostras de biópsias e mesmo de necropsias sejam conservadas apenas em formol, impossibilitando o envio para exame micológico (Miranda et al 2011).…”
Section: Discussionunclassified
“…A reação de Splendore-Hoeppli circundando as leveduras tem sido descrita como muito frequente na esporotricose humana (Vásquez-del-Mercado et al 2012, Mahajan 2014. Porém, não tem sido descrita na esporotricose felina (Miranda et al 2009, Schubach et al 2012) e também não foi vista nos gatos deste estudo.…”
Section: Discussionunclassified
“…The fungus grew best on Acacia melanoxylon, Cinnamomum camphora, Eucalyptus grandis, E. sideroxylon, and Ginkgo biloba [6,7]. This patient had been hurt while trimming Bougainvillea spp.…”
Section: Discussionmentioning
confidence: 99%